2006
DOI: 10.1186/1747-1028-1-16
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Ubiquitination regulates a host of cellular processes and is well known for its role in progression through the cell division cycle. In budding yeast, cadmium and arsenic stress, the availability of sulfur containing amino acids, and the intracellular concentration of S-adenosylmethionine are linked to cell cycle regulation through the ubiquitin ligase SCF Met30 . Regulation is achieved by ubiquitination of the transcription factor Met4. Met4 activity is controlled by a regulatory K48-linked ubiquitin chain th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
34
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 52 publications
0
34
0
Order By: Relevance
“…In the model system, yeast, a regulatory pathway connecting sulfur-containing metabolites, most notably methionine, with cell cycle regulation, has been suggested to respond primarily to S-adenosylmethionine (SAM) levels. [18][19][20] Furthermore, earlier studies showed that reducing SAM synthesis blocks proliferation of leukemic cells. 16,17 Therefore, we hypothesized that methionine dependence is a reflection of limiting SAM availability caused by reduced flux through the methionine metabolic pathway in Met-Hcy+ conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the model system, yeast, a regulatory pathway connecting sulfur-containing metabolites, most notably methionine, with cell cycle regulation, has been suggested to respond primarily to S-adenosylmethionine (SAM) levels. [18][19][20] Furthermore, earlier studies showed that reducing SAM synthesis blocks proliferation of leukemic cells. 16,17 Therefore, we hypothesized that methionine dependence is a reflection of limiting SAM availability caused by reduced flux through the methionine metabolic pathway in Met-Hcy+ conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Lowering the plasma methionine level concomitant with homocysteine supplementation in animal models causes regression of tumors, inhibition of metastasis and blocks growth of solid tumors and leukemia, but has no harmful effects on normal tissues. [12][13][14] The apparent hunger of cancer for methionine is also exploited by clinicians in tumor detection using 11 C-methionine as an alternative tracer for the glucose analog 18 F-FDG in positron emission tomography. 15 Molecular mechanisms describing how methionine dependency induces cell cycle arrest and apoptosis are unknown; however, the diverse ways in which a cell uses methionine are well-understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Central to this pathway is the regulation of transcription factor complexes containing the transactivating factor Met4 (2). Met4 regulation is also critical for the cellular response to cadmium and arsenic stress (3)(4)(5)(6)(7). Active Met4 induces expression of a group of genes, commonly referred to as MET genes, that are involved in sulfur assimilation and synthesis of sulfur-containing amino acids (1).…”
mentioning
confidence: 99%
“…In addition, Met4 promotes synthesis of the tripeptide glutathione for detoxification under cadmium and arsenic stress conditions by inducing GSH1 expression, a gene that encodes for ␥-glutamyl cysteine synthase, the rate-limiting enzyme in glutathione synthesis (4 -6, 8). Met4 regulation links these metabolic responses to regulation of cell proliferation, because activation of Met4 can induce a complex cell cycle arrest that involves down-regulation of G 1 and S phase cyclin expression, destabilization of prereplication complexes, a block of metaphase to anaphase transition, and reduction in translation (3,5,9,10).…”
mentioning
confidence: 99%